Strategic Content Investment and Platform Growth: A Case Study of Netflix’s Physical 100 - Ko, Audrey (Advances in Social Sciences Research Journal, 2026)
Netflix, operating in over 190 countries, has evolved from a DVD rental service into a leading global streaming platform by consistently identifying and capitalizing on emerging market trends. In recent years, the company has expanded its investment in original Korean content, including the reality competition series Physical: 100. The show’s global popularity, reflected in multiple renewals, underscores the growing influence of localized content in driving international audience engagement. This study evaluates the strategic value of such investments by examining whether continued funding of Physical: 100 represents a sustainable long-term growth strategy for Netflix. Through an analysis of content strategy, audience engagement, financial performance, and brand positioning, the paper explores the role of original programming in supporting long-term expansion and competitive advantage in the streaming industry.